The human ATF1 rs11169571 polymorphism increases essential hypertension risk through modifying miRNA binding. Issue 16 (3rd July 2015) - Yang, Sibao; Gao, Yongjian; Liu, Guohui; Li, Jiayu; Shi, Kaiyao; Du, Beibei; Si, Daoyuan; Yang, Ping
Abstract : Activating transcription factor 1 (ATF1) may be involved in essential hypertension (EH) by induction of NADPH oxidase 1 (NOX1) and radical oxygen species (ROSs) production. Abnormal expression of ATF1 was found in EH in previous microarray analysis. Here we tested whether a single nucleotide polymorphism (SNP) located in the 3′‐untranslated region (3′UTR) of ATF1 was associated with EH susceptibility by affecting microRNA (miRNA) binding. In silico analysis indicated that rs11169571 (T > C) was a candidate SNP to modulate miRNA: ATF1 mRNA complex, with the greatest changed energy for hsa‐miR‐1283, and the luciferase reporter analysis showed that miR‐1283 inhibited the activity of the reporter vector carrying –T allele, but not the –C allele. In addition, inhibition of miR‐1283 in HA‐VSMCs enhanced the expression of ATF1 mRNA as well as the ROS levels. Further case‐control study showed that rs11169571 was significantly associated with increased risk of EH. Finally, we observed an increased ATF1 protein level in peripheral blood of EH patients with CC carriers compared to TT carriers of rs11169571, with an intermediate ATF1 level in TC carriers. These results suggested that rs11169571 of ATF1 gene may be associated with EH, and the SNP‐modified posttranscriptional gene regulation by miRNAs could be a potentially pathogenetic mechanism of EH. Abstract : The CC genotype of rs11169571 may be associated with increased risk for EH. We first identified that hsa‐miR‐1283 was expressed by HAVSMCs. The ATF1 protein level in CC carriers was significantly higher than those in TT and TC carriers. The SNP‐modified posttranscriptional gene regulation by miRNAs could be a potentially pathogenetic mechanism of EH.